The Transformation of Indonesian Society’s Religious Responses to the Palestine-Israel Conflict: A Social and Religious Perspective: Transformasi Respons Keberagamaan Masyarakat Indonesia dalam Konflik Palestina-Israel: Perspektif Sosial dan Religius - fia, Nur Afiah (KURIOSITAS: Media Komunikasi Sosial dan Keagamaan, 2024)
The war conflict between Palestine and Israel which occurred in October 2023 has now attracted the attention of the whole world, such as Indonesia. As a result of this conflict, the Indonesian people condemned the heinous actions of the Israeli army which destroyed the Gaza Strip in Palestine. This research explains that the Indonesian people provide full support through altruistic behavior towards Palestine. This research used a mixed method with a total of 112 respondents who were Muslims and Christians from the Bugis, Makassar, Javanese, Sundanese, Timor Leste, Banjar, Manado, Batak and Aceh ethnic groups. The research results show that this war conflict made the Indonesian people give full support to Palestine. The form of support provided is in accordance with aspects of altruistic behavior, namely materially, helping spread news via social media as a form of support for Palestine, boycotting pro-Israel products so that the Israeli economy declines and makes it difficult to buy weapons. Apart from that, pay attention by condemning Israel's actions and feeling empathy. The reason people behave altruistically is because of their shared religion as Muslims, a sense of humanity, compassion and empathy, and a form of solidarity. The hope in this research is that the Indonesian people want peace and an end to war between countries in conflict.